Methods for monitoring scour from large-diameter heat probe tests - Amirmojahedi, M.; Akib, S.; Basser, H.; Raymond Ooi, C.H. (SAGE Publications (UK and US), 2016)
Scour is the main cause of bridge failures. Monitoring of bridge scour is an essential method to control the damages caused by flood events. In this study, a large-scale tube consisting of heating and temperature-sensing elements was developed, and its application for detecting saturated soil and water was analyzed. Laboratory experiments confirmed the applicability of the thermal sensor for scour-monitoring purposes. Three methods are proposed in this article for analyzing the data obtained from a heat probe. A linear relationship between temperature increase from the initial to the secondary time and heat production in the probe was observed, and a line that can be used to determine scour was introduced. This method is simple and can be used for low-cost, large-diameter heat probes that are easy to fabricate.